Development of polymeric drug delivery system using electrospun nanofibers for controlled release of multiple proteins - Mohd Amiruddin Fadzli, Mohamad Zaini (2010)
The purpose of the research is to develop a novel type of drug delivery carrier with the capability of encapsulating multiple drugs and release the drugs in controlled manner. Nanotechnology as a delivery platform offers very promising applications in drug delivery. Polymeric drug delivery devices were successfully developed via electrospinning technique using PCL, PLLA and PLLA-CL biodegradable polymers. Coaxial electrospinning configurations was used to encapsulate three proteins which are BSA, lysozyme and IgG into the electrospun nanofibers. Using the configuration, two separate polymers solutions flowed through two different capillaries which are coaxial with a smaller capillary inside a larger capillary. A number of processing parameters were investigated during the electrospinning process which are formulation of drug loading, the type of polymer and drug and the concentration of polymer and drug. The morphology of the electrospun nanofibers was analyzed using Scanning Electron Microscopy (SEM). The mechanical property was analyzed by using tensile strength and UVSpectrophotometer was used to study the proteins release profile. The results showed that the incorporated proteins could be controlled release by adjusting the process parameters and the proteins structure and bioactivity are maintained. Polymeric drug delivery device is able deliver a pre-determined amount of drug over specific amount of time in a predictable manner. It can improve the effectiveness of drug therapy by increasing the therapeutic activity and reducing the number of drug administrations.